Orbis [games] - Armstrong, Tim; Tosello, Davide (JD Editions - SPACE Cowboys, 2018)
"You are a god! Lands populated with worshipers are lost in the aether. Select and assemble these regions to create your own world. Villages, monuments, forests, rivers, or even volcanoes, it's up to you to create the most beautiful universe"--Container